2014
DOI: 10.1177/0020872813500804
|View full text |Cite
|
Sign up to set email alerts
|

Importing Western values versus indigenization: Social work practice with ethnic minorities in Hong Kong

Abstract: Serious debate about the indigenization of social work has transpired recently. This article argues that by taking indigenization as an interactive and non-linear process that helps cultivate a multicultural social work practice within a society, importing Western social work practice and indigenization are compatible. In particular, this article attempts to illustrate the compatibility by analyzing how political activists employ Western values and practice, the universal human rights discourse, and mainstream… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Even within the Han Chinese population, in other Chinese regions (e.g. Hong Kong), there may be some different epistemological discussions compared to those in mainland China, which may guide their social work research and practice differently (Law and Lee, 2016). Therefore, how unique contexts in different Chinese regions influence the epistemology of social work should also be explored to further enrich this discussion and better serve different Chinese populations.…”
Section: Discussionmentioning
confidence: 99%
“…Even within the Han Chinese population, in other Chinese regions (e.g. Hong Kong), there may be some different epistemological discussions compared to those in mainland China, which may guide their social work research and practice differently (Law and Lee, 2016). Therefore, how unique contexts in different Chinese regions influence the epistemology of social work should also be explored to further enrich this discussion and better serve different Chinese populations.…”
Section: Discussionmentioning
confidence: 99%
“…It could be argued that privileging children’s accounts has privileged Western ideals of children’s rights. But the UNCRC offers a framework for the critical analysis of power structures inherent in systems of cultural beliefs and values (Law and Lee, 2014). And its use in this study respects the global definition of social work that emphasises the use of theories and indigenous knowledge to engage people and structures to address life challenges and enhance well-being (IFSW, 2014).…”
Section: Concluding Discussionmentioning
confidence: 99%
“…There are still those who argue that the Confucian belief in strict authority and submission to parental will, whether through trust or fear, contributes to family harmony and happiness (Lu, 2001). But Law and Lee (2014) argue the value of the UNCRC in questioning long held and easily reproduced power structures. In this way the study reported here represents a way of disturbing thinking about children's rights in order to inform policy and practice in residential care settings.…”
Section: Children's Rights In Contextmentioning
confidence: 99%
“…The social work profession in Hong Kong has been mostly serving the ethnic majority (Hong Kong Chinese), in addition to immigrants/ethnic minorities (e.g. mainland Chinese, South Asians, and to a lesser degree Caucasians), through a hybrid approach of Western values (Law and Lee, 2016) imported from Britain, during its colonization of the territory, and Confucianism (Chui, 2014; Tsang et al, 2008). Hong Kong’s British colonial history and its reunification with the People’s Republic of China, in conjunction with sociocultural traditions, education, politics, and religious and belief systems, have shaped Hong Kong, tying societal values to hierarchy and sufficiency more so than equality and fairness within a society (Chiu and Walker, 2007).…”
Section: The Social Work Profession and Serving Ethnic Minorities In Hong Kongmentioning
confidence: 99%
“…Meanwhile, it is reasonable to challenge the common notion of a culturally unresponsive Hong Kong social work education system where ‘social work training has been narrowly indigenized to suit Hong Kong Chinese, and later, Mainland Chinese immigrants’ (Law and Lee, 2014, 2016: 61). Given ethnic minorities’ growing numbers, the lack of preparedness of social workers for serving this population is dismaying.…”
Section: The Social Work Profession and Serving Ethnic Minorities In Hong Kongmentioning
confidence: 99%